Characterizing the sensorimotor domain in schizophrenia spectrum disorders - Fritze, Stefan; Sambataro, Fabio; Kubera, Katharina Maria; Brandt, Geva A.; Meyer-Lindenberg, Andreas; Wolf, Robert Christian; Hirjak, Dusan (European archives of psychiatry and clinical neuroscience, 2022)
The rapidly evolving field of sensorimotor neuroscience reflects the scientific and clinical relevance of sensorimotor abnormalities as an intrinsic component of the disease process, e.g., in patients with schizophrenia spectrum disorders (SSD). Despite previous efforts, however, prevalence rates and relationships between different categories of sensorimotor abnormalities in SSD patients are still subject of ongoing debate. In this study, we examined five different categories of the sensorimotor domain (Neurological soft signs (NSS), parkinsonism, catatonia, akathisia, and tardive dyskinesia) according to well-established clinical ratings scales and the respective cut-off criteria in a sample of 131 SSD patients. We used a collection of statistical methods to better understand prevalence, overlap and heterogeneity, as well as psychopathological and cognitive correlates of sensorimotor abnormalities. 97.7% of the SSD patients considered by this study exhibited at least one categorically defined sensorimotor abnormality that tended to co-vary within three different sensorimotor subgroups (moderate, hyperkinetic and hypokinetic). Finally, hyperkinetic and hypokinetic groups differed significantly in their neurocognitive performance compared with the moderate group. The results suggest different patterns of clinical overlap, highlight the relationship between sensorimotor and cognitive domain and provide clues for further neurobiological studies.
Online veröffentlicht: 27. November 2021
Gesehen am 16.02.2023